2019
DOI: 10.4314/jab.v134i1.9
|View full text |Cite
|
Sign up to set email alerts
|

Dietary potassium diformate (Formi) supplementation on juvenile white shrimp (<i>Litopenaeus vannamei</i>) diets for growth and survival support

Abstract: Objective: This feeding trial was designed to assess the effects of formi (Dietary potassium diformate) supplementation in shrimp diet on growth and survival of white shrimp, Litopenaeus vannamei. Methodology and results: Seven isonitrogenous diets were formulated with graded formi levels of 0, 1, 2, 4, 8, 14 and 20 mg kg-1 of dry diet, respectively. Shrimps were randomly allocated to twenty four (24) 50 l aquariums (10 shrimps of 0.82 ± 0.08 g per aquarium, eight treatments and three replicates). Water salini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…Nevertheless, the results of our study shows that the growth parameters were not affected either by the proteins levels of the diet nor by the various K-diformate levels supplementation. Similar findings are reported in our previously study on the same species (Ly et al, 2019).…”
Section: Effects Of K-diformate Supplement On Body Colour After Cookingsupporting
confidence: 93%
“…Nevertheless, the results of our study shows that the growth parameters were not affected either by the proteins levels of the diet nor by the various K-diformate levels supplementation. Similar findings are reported in our previously study on the same species (Ly et al, 2019).…”
Section: Effects Of K-diformate Supplement On Body Colour After Cookingsupporting
confidence: 93%
“…The moisture of the diets was less than 14%, preventing the possible appearance of aflatoxins generated by the fungus Aspergillus flavus (Yu et al 2018). Moreover, leaching of the feedstuffs was less than 15%, which suggests no loss of nutrients in the water (Ly et al 2019), and that organisms had complete access to all the nutrients present in the feed pellets. In this study, shrimp fed with microalgaeenriched diets grew slightly faster than those in control, with the following descending order: D1, D3, and DC.…”
Section: Discussionmentioning
confidence: 99%
“…Hardi et al [ 21 ] explained that the combination of Boesenbergia pandurate , Z. zerumbet , and S. ferox effectively prevents infection with Aeromonas hydrophila and Pseudomonas sp., and modulates the immune system of tilapia, Oreochromis niloticus . However, studies highlighting the potential of phytobiotics have not been reported in white shrimp, although compound derivatives of phytobiotics have been previously reported [ 22 ].…”
Section: Introductionmentioning
confidence: 99%